Yaqui Delgado wants to kick your ass : the graphic novel - Vargas, Mel Valentine; Medina, Meg (Candlewick Press, 2023)
It's the beginning of sophomore year, and Piedad "Piddy" Sanchez is having a hard time adjusting to her new high school. Things don't get any easier when Piddy learns that Yaqui Delgado hates her and wants to kick her ass. Piddy doesn't even know who Yaqui is' never mind what she's done to piss her off. Rumor has it that Yaqui thinks Piddy is stuck-up, shakes her stuff when she walks, and isn't Latina enough with her white skin, good grades, and no accent. And Yaqui isn't kidding around, so Piddy better watch her back. At first, Piddy is more concerned with learning about the father she's never met, navigating her rocky relationship with her mom, and staying in touch with her best friend, Mitzi. But when the harassment escalates, avoiding Yaqui and her gang takes over Piddy's life. Is there any way for Piddy to survive without closing herself off from those who care about her--or running away? More relevant than ever a decade after its initial publication, Mel Valentine Vargas's graphic novel adaptation of Meg Medina's ultimately empowering story is poised to be discovered by a new generation of readers.